Future-ready crops, genetic variability in lima bean seeds - Souza, Jardel da Silva [UNESP]; Rodrigues, Lais Nóbrega; Ferreira, Lais Thomaz; Unêda-Trevisoli, Sandra Helena [UNESP]; Nascimento, Naysa Flávia Ferreira Do (Universidade Estadual de Maringa, 2024)
Lima bean cultivation has not received proper national and regional attention by research agencies, impairing the knowledge of the agronomic characteristics and its potential, information that is essential for the selection and launching of superior genotypes. The objective of this work was to characterize the seeds of 17 lima bean genotypes produced by family farmers in Paraíba State. The characterization was based on the descriptors for Phaseolus lunatus. A completely randomized design was used with 15 replicates. Data were submitted to analysis of variance with a subsequent grouping of means by the Scott-Knott test at 1% of probability. For analysis of the genetic diversity, the Tocher method was used based on the generalized Mahalanobis distance. There is variability among the genotypes. According to the means test, genotype 10 has a higher seed length, width, and weight. Considering the diversity among the groups and aiming to select light-colored and higher means of the evaluated traits, the selection of genotypes 8, 13, 4, and 10 is recommended to establish a breeding program that satisfies both the consumer and the producer.
Keywords: genetic diversity; Phaseolus lunatus; plant breeding